Lingkungan sebagai Media Penunjang Efektivitas Pembelajaran Bahasa Arab di Pondok Pesantren Al-Iman Ponorogo - Abdul Qodir Jailani; Ahmad Minhajul Abror (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2020)
This study aims to determine the environment as learning media of Arabic teaching, in two cases: (1) the important role; (2) the advantage & disadvantage advantages and disadvantages in utilizing the environment. Research conducted in in the ‘Al-Iman’ Islamic Boarding School, Ponorogo. The method used is descriptive-qualitative. The results indicate that: (1) The environment has an important role as a medium to support the effectiveness of Arabic learning, through the design of Arabic language habituation activities in the Boarding school environment. (2) The advantage and disadvantage can be identified in the use of the environment as a medium for learning Arabic. The advantages are: a) learning activities are more interesting and not boring, b) the nature of learning will be more meaningful, c) learning activities are more comprehensive and more active , d) learning resources become richer, e) students are also more able to understand and appreciate the aspects of life in their environment. The drawbacks are: a) limited preparation, b) there is an assumption that learning in the environment requires a relatively long time, c) many teachers still have a narrow view that learning is only done in the classroom.